Double Sign Reversal of the Hall Voltage in Bi2Sr2CaCu2O8+d Thin Film - dela Cruz, Aaron Paul; de la Cruz, Clarina; Sarmago, Roland (Science Diliman: A Journal of Pure and Applied Sciences; Vol 15 No 2 (2003), 2012)
Hall measurement was done on a Bi2Sr2CaCu2O8+d liquid phase epitaxy (LPE) thin film. The Hall voltage, VH, was obtained using the method of magnetic field direction reversal. Below the critical temperature, it was found that VH changes sign from positive to negative until it reaches a negative dip, after which it increases again to become zero and undergo a second sign change. With decreasing applied magnetic field, this dip was observed to become more prominent and greater in magnitude and to shift to lower temperatures. The sign change is explained by considering that the Hall field consists of two anti-parallel components: one is attributed to the deflection of the charge carriers by the Lorentz force, and the other is attributed to the dynamic motion of vortices in the mixed state.